Pembelajaran PPKN untuk Meningkatkan Sikap Nasionalisme Siswa Sekolah Dasar - Ziyadatul Hikmah, Neyla; Setya Nugroho, Arya (EduInovasi: Journal of Basic Educational Studies, 2024)
In the era of globalization, primary school students are increasingly exposed to various foreign cultural influences. foreign cultural influences. This has the potential to shift the values of nationalism that have been inherited by the predecessors. Therefore, there needs to be a systematic and sustainable effort to systematic and sustainable efforts to strengthen students' nationalism attitudes from an early age. early age. Creative and innovative Civics learning is expected to be a solution to overcome these challenges. solution to overcome these challenges. This research uses the Systematic Literature Review (SLR) method method with PRISMA (Preferred Reporting Items For Systematic Reviews And Meta-Analyses) which is carried out in a systematic way or following stages. The results showed that the application of Civics learning can shape the attitude of nationalism, including: love for the country and nation, willingness to sacrifice, tolerance, pride in diverse cultures and respect for the services of heroes. This research concludes that innovative and contextualized Civics learning is very effective. Recommendations are given to teachers to continue developing relevant and interesting learning methods relevant and interesting learning methods to strengthen national values among students from an early age. from an early age.